Pengurangan Sampah Makanan dalam Bisnis Kuliner Menggunakan Konsep E-Marketplace pada Aplikasi Mobile - Jessica Clarensia Suko; Djoni Haryadi Setiabudi; Justinus Andjarwirawan (Jurnal Infra, 2022)
Food waste has a lot of negative impact on various aspects. The two biggest contributor of food waste are domestic food waste and food service food waste that come from foods that are unsold. There are a few mobile applications that help reducing food waste on a domestic level using food sharing between individuals, but it didn’t work effectively due to lack of trust. To resolve that, a mobile application with an e-marketplace concept will be created to reduce food waste that focuses on culinary businesses (food services) level. With e-marketplace concept, the individual who has the role to give the food to the consumers will be culinary businesses that used to make foods on day to day basis and have their own business reputation, so that hopefully it will increase the trust of the consumers on receiving leftover foods (unsold foods). The application was tested on two culinary businesses in Surabaya with the first culinary business being a small culinary business and not very well known by the public, while the second culinary business is a large and very well-known culinary business among the public. The result shows that the application can reduce food waste as much as 5% on the first culinary business, but the application has failed to reduce the food waste of the second culinary business. On the other hand, the application managed to increase the trust of the consumers on buying and accepting the leftover foods although there is culinary business that the consumers didn’t know before.